Microarray Analyses of Grain Filling in Malaysian Indica Rice Varieties (Oryza Sativa L.) Mr84 And Mr219 - Teo, Chin Jit (2009)

(untitled)
Rice is a dominant staple food in Asia, including Malaysia. In this study, microarray analysis has been undertaken to identify the genes that were expressed at different stages of rice grain filling in MR219 and MR84 as it is a vital factor that affects the yield of rice directly. Two microarrays were used in this present study: cDNA microarray developed from 3840 PCR-amplified cDNAs from flag leaves and panicles; and commercial NSF 20 K rice oligonucleotide array. cDNA microarray analysis of panicles at 1, 5, 10 and 15 days after heading (DAH) of MR219 compared to heading revealed that a high proportion of storage proteins (glutelin and prolamin) were differentially expressed at 5, 10 and 15 DAH compared to heading in MR219. To compare the expressed genes in MR219 and MR84 at early grain filling period (5 and 10 DAH), microarray data generated from NSF 20K rice oligonucleotide array was analyzed using limmaGUI. Differentially expressed genes at 5-10 DAH from both MR219 and MR84 exhibited diversified functions, suggesting that rice grain filling is a complex biological process involving many different biochemical pathways. Genes encoding transcripts related to transcriptional regulation and signal transduction were differentially expressed at 5 and 10 DAH. In MR84, transcriptional factor EREBP, ethylene receptor, ERF-like protein and 1-aminocyclopropane-1-carboxylate oxidase 1 were up-regulated at 10 DAH while other transcription factors such as RING finger, zinc finger, GRAS family transcription factor were up-regulated in MR219. The up-regulation of genes related to sugar signaling and sensing may correlate to the assimilate partitioning and transport which occurred during 5-10 DAH in both varieties. Changes in gene expression caused by „varieties‟ and „developmental stage‟ effects involved transcripts related to stress and defense response, signal transduction and assimilate transportation in MR84 only. The expression patterns of 2 out of 3 selected genes examined were consistent when analyzed with microarray and RT-PCR. Southern analyses showed that putative ethylene responsive transcriptional coactivator and putative ABI3 interacting protein 2 may exist in more than one copy in the genome of both MR84 and MR219 whereas putative BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1 precursor may be a single copy gene in both varieties. Real time RT-PCR analysis demonstrated that putative BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1 precursor and putative ethylene responsive transcriptional coactivator were differentially expressed at heading, fertilized and 9-12 DAH compared to booting in MR84 and MR219.